Lipid metabolism and tumor immunotherapy - Wang, Yue; Guo, Zongjin; Isah, Adamu Danbala; Chen, Shuangwei; Ren, Yongfei; Cai, Huazhong (Frontiers in Cell and Developmental Biology, 2023)
In recent years, the relationship between lipid metabolism and tumor immunotherapy has been thoroughly investigated. Accumulating studies show that abnormal gene expression and metabolites related to fatty acid synthesis or fatty acid oxidation affect tumor metastasis, recurrence, and drug resistance. Tumor immunotherapy that aims to promote anti-tumor immune response has greatly improved the outcome of tumor patients. However, lipid metabolic reprogramming in tumor cells or microenvironment-infiltrated immune cells can influence the antitumor response of immune cells and induce immune evasion. The recent increase in the prevalence of obesity-related cancers has drawn attention to the fact that obesity increases fatty acid oxidation in cancer cells and suppresses the activation of immune cells, thereby weakening anti-tumor immunity. This review explains the changes in lipid metabolism in the tumor microenvironment and further describes the relationship between lipid metabolic reprogramming and tumor immunotherapy.